27Al and 45Sc NMR Spectroscopy on ScT2Al and Sc(T0.5T′0.5)2Al (T = T′ = Ni, Pd, Pt, Cu, Ag, Au) Heusler Phases and Superconductivity in Sc(Pd0.5Au0.5)2Al12. Issue 2 (27th January 2015) - Benndorf, Christopher; Niehaus, Oliver; Eckert, Hellmut; Janka, Oliver
Abstract The intermetallic Heusler compounds with ScT2Al and Sc(T0.5T′0.5)2Al composition with T = T' = Ni, Pd, Pt, Cu, Ag, Au were synthesized from the elements by arc melting. They crystallize in the cubic MnCu2Al type structure, space group Fm<alternatives> <![CDATA[$\bar{3}$]]> <inline-graphic xlink:href="ark:/27927/pgh3xswfb4d" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>m. The unit cell parameters were determined by powder X‐ray diffraction and the structure of Sc(Pd0.5Au0.5)2Al was refined on the basis of single‐crystal X‐ray diffraction. While the majority of the compounds show Pauli‐paramagnetism, ScAu2Al and the newly synthesized solid solution Sc(Pd0.5Au0.5)2Al exhibit superconductivity with transition temperatures of TC = 4.4 K and TC = 3.0(1) K, respectively. The superconducting state of Sc(Pd0.5Au0.5)2Al was also investigated by electrical resistivity measurements. All the synthesized compounds were furthermore studied by 27Al and 45Sc MAS‐NMR spectroscopy. The resonance shifts of the synthesized compounds were determined and in Sc(Pd1–xAux)2Al a linear relationship between the resonance shifts and the composition was found. Line broadening effects and enhanced quadrupolar interaction strengths observed in the mixed samples can be attributed to the effect of Pd/Au mixing on the 8c Wyckoff site. The NMR spectroscopic data give no clear evidence for or against Sc/Al site disordering.